The Influence of Individual Creativity and Product Innovation on Coffee Shop Barista Career Development in Pekanbaru - Kiki Joesyiana; Arie Rifa'i Harahap; Rofiq Noorman Haryadi (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
This research is a follow-up research that was previously carried out by the author, the difference lies in the research object. If the object of the previous research was coffee shops in the city of Pekanbaru by analyzing the creativity and innovation that coffee shop entrepreneurs must have, while in this research the object is the baristas owned by coffee shops. Individual creativity, product innovation and barista career development are very important aspects to be the main focus for coffee shops in Pekanbaru city for the continuity of the business they run. In order for the career development of coffee shop baristas to be maximized and make the baristas proud of themselves because their skills are recognized by coffee shop businesses, it is necessary to increase individual creativity so that they can produce product innovations that are getting better over time. Good career development for coffee shop baristas is one that can provide high self-confidence and ultimately be able to compete with international and global baristas, thus automatically having a very positive impact on the coffee shop business itself. To be able to realize good career development for coffee shop baristas in the city of Pekanbaru, special attention is also needed regarding how to increase individual creativity which will then be able to give birth to product innovations that better suit the needs and desires of consumers from time to time. From the results of these thoughts, researchers are interested in discussing and finding out how and to what extent individual creativity and product innovation can influence the career development of a coffee shop barista. The analysis in this research uses the multiple linear regression method, from the results of SPSS data processing the coefficient of determination value in the strong category is 0.706, which means that individual creativity and product innovation have a 70.6% influence on the career development of coffee shop baristas in the city of Pekanbaru.